INTELLECTUAL ECONOMIC DEVELOPMENT: COST AND EFFICIENCY INDICATORS - Yakymchuk, Alina; Valyukh, Andriy; Poliakova, Nataliia; Skorohod, Iryna; Sak, Tetiana (ECONOMICS - INNOVATIVE AND ECONOMICS RESEARCH JOURNAL, 2023)
Innovation and economic development go hand in hand. Innovation is the key to economic growth and prosperity. In the current era of globalization, countries that invest in research and development (R&D) and innovative activities are more likely to achieve sustained economic growth and competitiveness in the global marketplace. The purpose of this study is to analyze the values of the International Intellectual Property Index in different countries of the world and compare these data; to establish the relationship between the financial and economic development of the territories, expenses on intellectual research and the international index of intellectual property of the states using different approaches and methods. This article aims to explore the positive experience of intellectual economic development in the world, with a focus on the costs of innovation. The Global Innovation Index (GII) ranks countries based on their innovation capabilities, such as human capital, research and development, institutions, infrastructure, market sophistication, and business sophistication. According to the GII 2021 report, the top five most innovative countries are Switzerland, Sweden, the United States, the United Kingdom, and the Republic of Korea. All this points to the need for the development of innovative and intellectual developments in Ukraine. Such intellectual developments are of particular importance in the conditions of war and are necessary for strengthening the security indicators of the state, preserving the lives of the population in the conditions of missile attacks and destruction. In the world, intellectual economic development is seen as a key driver of economic growth and competitiveness.